Sex Ratio and Size at First Maturity of Snakehead Gudgeon (Giuris margaritacea) Caught with Gillnets at Bolano Sau Lake, Parigi Moutong District - Putra, Aswad Eka; Nurdin, Muh. Saleh; Hasanah, Nur; Ndobe, Samliok; Mansyur, Kasim (AgriSains, 2020)
The research aimed to sex ratio and size at first maturity of snakehead gudgeon at Bolano Sau Lake. The research was conducted at Bolano Sau Lake from August to December 2019. Snakehead gudgeon samples were obtained from the fishermen using a gillnet with a mesh size 2Â½-3Â½ inches. Sample analysis was carried out at the Water Quality Laboratory, State College of Fisheries and Marine, Palu. The difference in sex ratios of snakehead gudgeon used the Chi-square test, while the size at first maturity was estimated based on the Spearman - Karber method. Snakehead gudgeon caught on a gillnet in Bolano Sau Lake measuring 79-163 mm. The sex ratio between males and females is not balanced where males are more dominant in females. The size at first maturity was 119.19 mm. Suggestion minimum legal size > 120 mm. The use of gillnets in snakehead gudgeon fishing activities has an effect on the balance of male and females, but is very selective with size.